The Effect of Giving Warm Ginger in Reducing Emesis Gravidarum in 1st Trimester Pregnant Women - Maridanti, Lina; Anwar, Ade; Fairuza, Filda; Safitri, Resti; Rezaldi, Firman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Due to an increase in the hormone estrogen and progesterone produced by Human Chronic Gonadotropin (HCG), which causes emesis gravidarum, during pregnancy, the mother experiences hormonal changes. This study means to decide the impact of giving warm ginger in diminishing emesis gravidarum in pregnant ladies in the principal trimester PMB Lilis Nurhasanah, S.ST., Keb., Bd. SKM 2024. This exploration utilizes a Semi Trial technique with a One Gathering Pretest Posttest plan. This study's participants were pregnant women in their first trimester who had emesis gravidarum at PMB Lilis Nurhasanah, S.ST., Keb., Bd. SKM upwards of 30 respondents. The examining strategy in this examination is Complete Testing. Shapiro-Wilk normality test analysis yielded sig data (0.05). The Wilcoxon test has a p-worth of 0.000, and that implies there is an impact of giving warm ginger in diminishing emesis gravidarum in first trimester pregnant ladies. This end shows that there is an impact of giving warm ginger in lessening emesis gravidarum in first trimester pregnant ladies at PMB Lilis Nurhasanah, S.ST., Keb., Bd. SKM 2024.